2021
DOI: 10.3389/fonc.2020.570916
|View full text |Cite
|
Sign up to set email alerts
|

The tRNA-Derived Fragment-3017A Promotes Metastasis by Inhibiting NELL2 in Human Gastric Cancer

Abstract: tRNA-derived fragments (tRFs) are a new classification of small non-coding RNAs (sncRNAs) derived from the specific cleavage of precursors and mature tRNAs. Accumulating recent evidence has shown that tRFs are frequently abnormal in several cancers. Nevertheless, the role of tRFs in gastric cancer and its mechanism remain unclear. In this study, we found abnormal expression of tRF-3017A (derived from tRNA-Val-TAC) in gastric cancer tissues and cell lines and confirmed its effect on promoting the invasion and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 60 publications
1
38
0
Order By: Relevance
“…demonstrated that tRF-3019a enhanced cell proliferation, migration, and invasion by targeting FBXO47, and it might serve as a potential diagnostic biomarker for GC ( 36 ). Similar results were found that tRF-3017A might play an important role in promoting migration and invasion by silencing NELL2 in GC ( 37 ). In this study, tRFs were screened from GC tissues by high-throughput sequencing.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…demonstrated that tRF-3019a enhanced cell proliferation, migration, and invasion by targeting FBXO47, and it might serve as a potential diagnostic biomarker for GC ( 36 ). Similar results were found that tRF-3017A might play an important role in promoting migration and invasion by silencing NELL2 in GC ( 37 ). In this study, tRFs were screened from GC tissues by high-throughput sequencing.…”
Section: Discussionsupporting
confidence: 86%
“…tRF-3017A was highly expressed in tissues and cell lines of GC and was positively correlated with lymph node metastasis. It may be that tRF-3017A promotes the migration and invasion of GC cells by silencing the tumor suppressor NELL2 ( 37 ). In the previous study, our team also found that serum hsa_tsr016141 has good stability and specificity and could be used for dynamic monitoring of patients with GC ( 38 ).…”
Section: Introductionmentioning
confidence: 99%
“…84 A direct correlation of tRNA fragments with metastasis and cell proliferation has been shown recently. Tong et al 45 have reported that tRNA-Val TAC -derived tRF-3017A promotes metastasis in gastric cancer by regulating the NELL2 tumor suppressor gene. 45 The tumor suppressor transcription factor (TF) RUNX1 plays a significant role in initiation and metastasis of breast cancer.…”
Section: Tsrnas and Cancermentioning
confidence: 99%
“…Meanwhile, the metastasis regulatory functions of tsRNAs are also found in other malignancies. tRF-3017A was found to silence the tumor suppressor NELL2 through an AGO-dependent mechanism, thereby promoting the invasion and migration of gastric cancer cells [ 69 ]. tRF-17 was found to act as an invasion inhibitor by regulating the THBS1/TGF-β1/smad3 axis in breast cancer cells [ 70 ].…”
Section: Tsrnas and Cancer Hallmarksmentioning
confidence: 99%